Ice action on Nanisivik wharf, winter 1979–1980 - Frederking, R.; Nakawo, M. (Canadian Journal of Civil Engineering, 1984)
During the period December 1979 to June 1980, five visits were made to observe and measure ice behaviour around the wharf at Nanisivik, on Baffin Island. The measurements included ice thickness, temperature, salinity, and density, as well as horizontal movements of the ice cover. In March 1980, additional measurements and observations were made of tides, rotations of the ice sheet, and grain structure of the ice. A model for the formation of an active zone of ice between the wharf and the adjacent ice cover has been proposed, based on the observed evolution of ice conditions and internal structure of the active zone. Horizontal growth of the active zone displaces the adjacent ice cover away from the wharf, and in so doing, generates ice pressures estimated at 69 kPa on the wharf. Key words: ice forces, wharves, ice behaviour, ice properties.